Allopurinol improves endothelial function and reduces oxidant-inflammatory enzyme of myeloperoxidase in metabolic syndrome - ŞENER, GÖKSEL (SPRINGER HEIDELBERG, 2008)
Objective In this study, we tested in patients with metabolic syndrome whether allopurinol through decreasing oxidative stress improves endothelial function, and ameliorates inflammatory state represented by markers of myeloperoxidase, C-reactive protein (CRP) and fibrinogen. Methods In a randomized, double-blind fashion; subjects with metabolic syndrome were treated with allopurinol (n = 28) or placebo (n = 22) for one month. Before and after treatment, blood samples were collected and the flow-mediated dilation (FMD) and isosorbide dinitrate (ISDN)-mediated dilation of the brachial artery were performed. Results Baseline clinical characteristics of the allopurinol and placebo groups demonstrated no differences in terms of clinical characteristics, endothelial function and inflammatory markers. After the treatment with allopurinol, FMD was increased from 8.0 +/- 0.5 % to 11.8 +/- 0.6% (P < 0.01), but there were no change in the placebo group. In both groups, ISDN-mediated dilation is unaffected by the treatment. As a marker of oxidative stress, allopurinol significantly reduced malondialdehyde. Moreover, myeloperoxidase levels were reduced by the treatment with allopurinol (56.1 +/- 3.4 ng/ml vs. 44.4 +/- 2.4 ng/ml, P < 0.05) but there were no change in the placebo group. Surprisingly, neither CRP nor fibrinogen levels were affected by the treatment in both groups. Conclusion Xanthine oxidoreductase inhibition by allopurinol in patients with metabolic syndrome reduces oxidative stress, improves endothelial function, ameliorates myeloperoxidase levels and does not have any effect on CRP and fibrinogen levels.
Keywords: metabolic syndrome; allopurinol; myeloperoxidase; endothelial dysfunction; C-reactive protein; SERUM URIC-ACID; C-REACTIVE PROTEIN; XANTHINE-OXIDASE; HYPOCHLOROUS ACID; OXIDATIVE STRESS; DYSFUNCTION; HEART; ATHEROSCLEROSIS; RISK; ASSOCIATION